Konversi agama: Tahap-tahap konversi agama - Akmala, Nida Azkia (Maliki Interdisciplinary Journal, 2025)
Religious conversion is a complex psychological and social phenomenon that reflects changes in individual beliefs as well as the accompanying internal and external dynamics. The study of religious conversion is essential within the field of the psychology of religion, as it provides an understanding of the factors that influence belief transformation, including emotional, social, and cultural aspects. This article aims to identify the stages in the process of religious conversion and to analyze the factors influencing it from a psychological perspective. The findings indicate that religious conversion is influenced by internal factors—such as emotional tension and the search for meaning in life—as well as external factors, including social invitations and religious traditions. The conversion process consists of five stages, ranging from a period of calm to the expression of conversion in an individual’s life. This study is expected to provide academic contributions and serve as a guide for practitioners in understanding and assisting individuals undergoing changes in religious belief.